Social Networking Websites and Their Effect in Contemporary Human Resource Management - A Research Approach - Aspridis, G.; Kazantzi, V.; Kyriakou, D. (Richtmann Publishing, 2013)
Social Media, the new term that has invaded our daily lives in high velocity, consists of social networking, playing interactivegames, making international friendships and communicating, in general, worldwide. On the other hand, Human Resources areoccupied with terms such as recruitment, career advancement, motivation, employability, evaluation. Those two seem sodifferent and diverse but nowadays a correlation and a parallel walk is occurring. Social Media sites such as Facebook,Linkedin, Twitter etc are currently being utilised as a company promotion tool under their will to reach in a personal way each'user' or as a possible employability entrance, and, in same recent cases, reason for dismissal. But how these two actuallycombine or better correlate? This latter in addition, firstly, to the way this relation is widely perceived by potential and currentemployees as well as companies' Human Resources departments and secondly, the emergence and application of all these inthe case of Greece, will be the research scope of this paper presenting the traditional way of recruitment and selection as wellas career advancement and evaluation through the basic principles of Human Resources Theory and practical experience, incorrelation with the will to explore and investigate the opportunity or not to utilise social media as an additional tool in order toadvance in a modern world of Human Resources.